The Filipino migration experience global agents of change - Roces, Mina 1959- (Ithaca Cornell University Press, 2022)
"This book documents the way Filipino migrants from the 1970s-2018 have become agents of change. Migrants critiqued institutions such the family and definitions of the feminine, they transformed social mores and inspired transnational business ventures, they altered the host countries through advocacy, and they revolutionized the homeland through diasporic philanthropy"
Introduction : Toward a History of Filipino Migrants as Agents of Change -- Migration and the Rethinking the Filipino Family, 1970s-2018 -- Challenging Constructions of Gender and Sexuality, 1980s-2018 -- Consumption and Social Change, 1980s-2018 -- The Impact of Consumption on Businesses, 1990s-2017 -- Filipina/o/x Americans as Community Historians, 1980s-2018 -- Advocacy and Its Impacts, 1970s-2000 -- Migrants and the Homeland, 1986-2018 -- Conclusion : Refusing to be Marginal.
Includes bibliographical references and index.
Keywords: Filipinos--Foreign countries--Social conditions--20th century -- Foreign countries -- Social conditions -- 20th century; Return migrants -- Philippines -- Social conditions -- 21st century; Social change -- Philippines; Philippines -- Emigration and immigration -- Social aspects